Every mother's son - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Jackals., 2021)
In Texas's Big Bend country, every man has a price. For crime lord Harry Holland and his ruthless gang of cutthroats, that price is $20,000--a ransom demand for the kidnapped daughter of a retired Army colonel. So far, neither the Army nor the Rangers have been have been able to penetrate Holland's guarded fortress. In desperation, the colonel turns to the Jackals. As a longtime friend, retired cavalry sergeant Sean Keegan is determined to bring the man's daughter back alive--with or without the ransom money--with help from his partners, former Texas Ranger Matt McCulloch and bounty hunter Jed Breen. When word gets out that the Jackals are on the case, all hell breaks loose. They're up against trigger-happy mercenaries, marauding Apaches, and one final, jaw-dropping surprise--a kidnapping victim who doesn't want to be rescued. This time, the Jackals have no one to save ... but themselves.